PENGARUH PARTISIPASI ANGGARAN, KOMITMEN ORGANISASI DAN MOTIVASI TERHADAP KINERJA MANAJERIAL INSPEKTORAT KABUPATEN PROBOLINGGO - Tatik Amani; Joni Hendra; Kholili Arsat Sukaji; Nurul Izzah (Universitas Muhammadiyah Jember, 2023)
Abstract : The aim of the research is to test and provide empirical evidence to what extent budgetary participation, organizational commitment and motivation affect the managerial performance of the inspectorate in Probolinggo Regency. Data collection used a questionnaire to all employees at the Inspectorate Office in Probolinggo Regency. The population and sample in this study used saturated sampling with a total of 37 respondents, namely all employees of class II, III and IV whose grouping consisted of two types, namely the male category and the female category. The research method is quantitative with data analysis using statistical procedures with validity, reliability, classical assumptions, multiple linear regression, coefficient of determination using SPSS aplication. The results of hypothesis testing of the independent variables, namely X1 (budget participation), X2 (organizational commitment) and X3 (motivation) in this study partially and simultaneously affect the dependent variable, namely variable Y (managerial performance) found in the Inspectorate of Probolinggo Regency with the result of determination is 67.2% independent variable. The test results indicate that there is a significant effect of the three independent variables on the dependent variable so that the Inspectorate Office in Probolinggo Regency should pay more attention to these variables in order to improve managerial performance and achieve organizational goals according to what has been set. Acknowledgments to all employees both class I, group II and group III who have helped and become respondents in this study. Keywords: Budget Participation, Organizational Commitment, Motivation and Managerial Performance. Abstrak : Tujuan penelitian yaitu menguji dan memberikan bukti empiris sampai dimana pengaruh persepsi anggaran, komitmen organisasi serta motivasi terhadap kinerja manajerial inspektorat di Kabupaten Probolinggo. Pengumpulan data menggunakan kuesioner kepada seluruh pegawai pada Kantor Inspektorat di Kabupaten Probolinggo. Populasi dan sampel dalam penelitian ini menggunakan sampling jenuh dengan jumlah responden 37 yaitu seluruh pegawai golongan II, III dan IV yang pengelompokannya terdiri dari dua jenis yaitu kategori laki-laki dan kategori perempuan. Metode penelitian yaitu kuantitatif dengan analisis data menggunakan prosedur statistik dengan uji validitas, reliabilitas, asumsi klasik, regresi linier berganda, koefisien determinasi dengan menggunakan aolikasi SPSS. Hasil uji hipotesis dari variabel bebas yaitu X1 (partisipasi anggaran), X2 (komitmen organiasi) dan X3 (motivasi) dalam penelitian ini berpengaruh secara parsial dan simultan terhadap variabel ikatan yaitu variabel Y (kinerja manajerial) yang terdapat di Inspektorat Kabupaten Probolinggo dengan hasil determinasi adalah 67,2% variabel bebas. Pada hasil uji tersebut menunjukkan adanya pengaruh ketiga variabel bebas signifikan terhadap variabel terikat sehingga sebaiknya Kantor Inspektorat di Kabupaten Probolinggo lebih memperhatikan variabel tersebut agar meningkatkan kinerja manajerial dan tujuan organisasi tercapai dengan baik sesuai yang ditetapkan. Ucapan terima kasih kepada seluruh pegawai baik golongan I, golongan II dan Golongan III yang telah membantu dan menjadi responden dalam penelitian ini. Kata Kunci: Partisipasi Anggaran, Komitmen Organisasi, Motivasi dan Kinerja Manajerial.